Power, Positionality, and Policymaking in Higher Education: Reflections on Student Lactation Support Initiatives - Whipps, Mackenzie; Dinour, Lauren; Vancour, Michele (Journal of Women and Gender in Higher Education, 2026)
In recent years, universities have extended lactation protections to students that have been traditionally afforded to paid employees only. Absent federal- and state-level regulation, this expansion has generally been piecemeal, taking place only when “breastfeeding advocates” request (or demand) those protections within their universities. Little research exists on these initiatives or about the breastfeeding advocates themselves. This article describes three examples of student lactation support initiatives on diverse U.S. university campuses. Using a comparative case study approach, the researchers examined the impact of positionality within higher education—and relative power afforded to different positions—on the initiatives and experiences of breastfeeding advocates. It is necessary to raise awareness and critically reflect on power structures to bring about change. The researchers found benefits of empowering students to engage in collective advocacy toward these ends, with practical implications for future U.S. lactation protection in academia. © 2026 NASPA—Student Affairs Administrators in Higher Education.
Keywords: dept.hhs

Community-engaged design of a virtual diabetes prevention program intervention with care coordination - LaMonaca, Katherine; Campbell-Britton, Meredith; Duffany, Kathleen O’Connor; Comerford, Beth P.; Morales, Sofia I.; Ayettey, Rockiy G.; Astudillo, Katia; Swansiger, Mary; Kidd, Claudette; Rue, Bailee; Santilli, Alycia; Njike, Valentine Y.; et al. (BMC Health Services Research, 2026)
The Diabetes Prevention Program (DPP) is an evidence-based approach to prevent Type 2 Diabetes (T2D), the leading cause of morbidity and mortality in the United States. Despite demonstrated benefits, acceptability and uptake of DPPs remain low, especially among communities with low incomes at increased risk for diabetes. The Yale-Griffin Prevention Research Center led the design of a community-engaged virtual DPP (vDPP) intervention and assessed its feasibility of implementation in two contrasting settings.
Keywords: Prediabetes; Prevention; Telemedicine; Type 2 Diabetes; dept.hhs

Cartwheels by Natalie Schriefer - Schriefer, Natalie (Flash Frog, 2025)
Nick’s millionth cartwheel looks like his first: He plants one hand on the grass and then, before I can catch his legs and help, he tumbles into a round-off. For a moment I’m taller than him, and I…
Keywords: dept.hhs

Re-Playing Majora’s Mask, College - Schriefer, Natalie (Medium, 2026)
The guard who calls you a child eventually recants.
Keywords: dept.hhs

Zelda With a Pearl Earring - Schriefer, Natalie (Medium, 2024)
After Nixeu’s “ZELDA [Girl with a Pearl Earring]”
Keywords: dept.hhs

Self-Portrait in the Key of Masc by Natalie Schriefer - Schriefer, Natalie (HAD, 2024)
In the style of WCW’s “This is Just to Say” Today I donated the red dress I wore to that holiday party which you were probably hoping I’d wear again but the truth is I hated the sweetheart neckl
Keywords: dept.hhs

’Backrooms’ Tests the Future of Horror Movies - Schriefer, Natalie (Bloomberg.com, 2026)
The film may determine how much Hollywood is willing to bet on other stories without a clear monster.
Keywords: A24; Backrooms; Bloomberg Graphics; Hollywood; Theater; culture; dept.hhs; gaming; graphic; indie games; internet; movies; opinion column

There's a Specific Type of Grief We Don't Talk About. Yoga Can Help You Process It. - Schriefer, Natalie (Yoga Journal, 2026)
Give yourself permission to feel everything.
Keywords: dept.hhs

Will CorePower Yoga Teachers Actually Go on Strike? - Schriefer, Natalie (Yoga Journal, 2026)
As February 1 draws closer, everyone is asking this question. Here's everything you need to know.

Gay Romance ‘Heated Rivalry’ Is Reigniting a Troubling Debate - Schriefer, Natalie (Bloomberg.com, 2025)
Heated Rivalry, based on the second book in Rachel Reid’s “Game Changers” series, has been a hit for HBO Max. Critics have called the gay romance about hockey players one of the best queer TV shows, praising it as “sexy” and “significant.” Beyond these glowing reviews, though, there is another discourse. Heated Rivalry’s success has reignited an unhealthy debate over who gets to tell the stories of marginalized communities — a debate that has proven harmful to closeted creatives in the past and
Keywords: Art; Career; Environment; Equality; Jordan; NETFLIX INC; NEW YORK TIMES CO-A; Rachel Reid; TWITTER INC; Youtube; dept.hhs; view

What I Learned When I Refused to Give Up on My Most Challenging Yoga Pose - Schriefer, Natalie (Yoga Journal, 2025)
A lesson on leaning into discomfort.
Keywords: dept.hhs

Why a Home Yoga Practice Is Just as Legit as Studio Practice - Schriefer, Natalie (Yoga Journal, 2025)
At-home yoga taught me about flexibility—and perfectionism, too.
Keywords: dept.hhs

Why This Round of Tariffs Feels So Personal - Schriefer, Natalie (Bloomberg.com, 2025)
The dreaded “T” word seems to be on everyone’s mind because consumers know it could mean paying more for what they love.
Keywords: China; Donald John Trump; Lifestyle; Policy; Politics; Raw Materials; Small Business; Trade War; Video Games; White House; dept.hhs; view

Avoiding the ‘Curse of Knowledge’ in Your Writing - Schriefer, Natalie (Inside Higher Ed)
When seeking an academic editor, you may want to consider a generalist, writes Natalie Schriefer, who suggests how to find the best one for your work. I became an academic editor by accident. In 2015, an acquaintance asked if I was up for some last-minute proofreading. He was an adjunct professor and the sole author on a short article. His revisions were due the next day, and he was nervous about his grammar, but he’d heard I had an English degree. Could he hire me? When I said yes, I thought I was agreeing to a one-off job. That it would turn into six years of us working together, and start my freelance editing career? The thought never crossed my mind.
Keywords: Career; Education; Events; Higher; Jobs; News; dept.hhs

Close Reading: HOW WRITING BOOK REVIEWS MADE ME a BETTER WRITER - Schriefer, Natalie (Poets & Writers Magazine, 2024)
Keywords: dept.hhs

How to Handle Online Harassment When It Happens to You - Schriefer, Natalie (Wired, 2024)
41% of adults in the US have been harassed online. If your mentions, inboxes, and DMs are blowing up with hateful comments, here are the technological and psychological tools you need to weather the storm.
Section: tags
Keywords: dept.hhs; how-to; mental health; online harassment; social media; twitter

Video Game Music: Science Explains Why Playing Final Fantasy Songs Is Good for Your Brain - Schriefer, Natalie (Inverse, 2024)
Musical memories are relatively unharmed by dementia.
Keywords: dept.hhs

Video Games and Resilience: Science Explains Why Playing Zelda Is Good For Your Brain - Schriefer, Natalie (Inverse, 2023)
Available to players of any skill level — no Twitch subscribers required.
Keywords: dept.hhs

Nintendo Has a Silent Problem With ‘Zelda’ Film - Schriefer, Natalie; CNN, sexuality She has written for; Think, NBC News; Insider; HuffPost; others. (Bloomberg.com, 2023)
A movie based on the popular video game will be inherently difficult because its recurring protagonist doesn’t speak. And developers have long preferred to keep it that way.
Keywords: Culture; Design; Generic 1st 'SI' Future; MAMMA MIA; MICROSOFT CORP; Markets; NETFLIX INC; NINTENDO CO LTD; Video Games; Women; dept.hhs; view

Funny Women: Query Letter for My Totally Publishable Novel - Schriefer, Natalie (The Rumpus, 2023)
(The previous sentence demonstrates both my market awareness and my forward thinking.)
Keywords: dept.hhs

How To Navigate Your Kid’s Coming Out - Schriefer, Natalie (Scary Mommy, 2024)
Five tips for straight parents on how to make the process a little easier – and what to say.
Keywords: dept.hhs

How A Book From 1985 Unexpectedly Changed My View On My Sexuality - Schriefer, Natalie (HuffPost, 2023)
“I expected a lot of things when I started the novel … but I didn’t think it would feel culturally relevant in 2023.”
Section: Culture & Arts
Keywords: dept.hhs

Opinion: The new Zelda has finally arrived. It’s time for a rethink on video games. - Schriefer, Natalie (CNN, 2023)
I was thrilled when Nintendo released “The Legend of Zelda: Tears of the Kingdom” in May. But the unfettered joy I feel playing Zelda today took me longer to acquire than all 900 Korok seeds. While my parents supported my playing video games growing up, so many others blamed them for ruining lives, writes Natalie Schriefer.
Keywords: dept.hhs

Driving Directions - Schriefer, Natalie (Word Sports, 2023)
START: END: Trumbull High School Sacred Heart University 72 Strobel Road
Keywords: dept.hhs

When the Little Things Matter - Schriefer, Natalie (Inside Higher Ed)
Getting your research published can feel overwhelming, writes Natalie Schriefer, who offers editing tips about references, citations, charts and formats to help you feel more confident submitting. Nothing is more daunting than pressing “send” on your first scholarly articles. It’s even more overwhelming when your institution doesn’t offer any internal support—and you essentially feel alone.
Keywords: Career; Education; Events; Higher; Jobs; News; dept.hhs

I Wrote About Not Shaving For A Month — And The Backlash Made One Thing Perfectly Clear - Writer, Natalie SchrieferGuest (HuffPost, 2023)
"Within an hour, I had a dozen emails. By the next morning, there were two dozen more — plus more than 100 Twitter notifications."
Section: HuffPost Personal
Keywords: dept.hhs

Author, Edit Thyself. - Schriefer, Natalie (ASEE Prism, 2023)
The article focuses on providing tips to academics for improving the quality and acceptance chances of their scholarly work during the publishing process. Topics discussed include the benefits of reading work aloud to catch errors, batching tasks like reviewing reference lists and in-text citations, and the importance of carefully formatting tables and figures according to publication guidelines.
Keywords: Editing; Oral reading; Punctuation; Tense (Grammar); dept.hhs

The five queer books that helped me come out | Xtra Magazine - Schriefer, Natalie (Xtra, 2022)
These five recent memoirs are queer books that helped me come out, echoing my own life, sometimes in unexpected ways
Section: Books
Keywords: dept.hhs

Learning Self-Compassion - Distancesays, November 20th-Critical (Into The Spine, 2022)
With a little help from Zelda.
Keywords: dept.hhs

Opinion | The reckless way I avoided student debt - Schriefer, Natalie (NBC News, 2022)
I worked three jobs to avoid student debt. Many students find themselves in a similar vulnerable spot, choosing to either face burnout now or later.
Keywords: dept.hhs

So They Didn’t Say Yes: How A Scholarship Rejection Taught Me to Work Smarter - Schriefer, Natalie (Author, 2022)
Three years ago, I graduated from my MFA program. I wanted to hit the ground running, so right from the start, I crafted myself a ritual: around the first of each month, I’d spend a morning scouring listservs and social media for writing opportunities. I tracked submissions calls, literary magazine
Keywords: dept.hhs

For Kids in the Hospital, Video Games Are Part of Recovery - Schriefer, Natalie (Wired, 2022)
In-house gaming technology specialists play with and support the youngest patients. Plus, research shows that playtime gives literal health points.
Section: tags
Keywords: charity; dept.hhs; gaming culture; health care; video games

Here's Why The 'Don't Say Gay' Bill Won't Work - Schriefer, Natalie (Ms. Magazine, 2022)
The flaw in Florida’s “Don’t Say Gay” bill and Texas's anti-trans child abuse directive: They will hurt LGBTQ kids, students and teens.
Keywords: dept.hhs

How to Cope With Post-Game Depression - Schriefer, Natalie (Wired, 2022)
Congratulations, you beat your favorite video game. Now it’s time to beat the feelings of emptiness.
Section: tags
Keywords: dept.hhs; gaming culture; mental health; psychology; video games

The Complicated Queerness in Breath of the Wild - Schriefer, Natalie (Medium, 2021)
Let’s talk about Bolson and Vilia. CW: Transphobia
Keywords: dept.hhs

The English Teacher Who Taught Me How to Hear - Schriefer, Natalie (The Wisdom Daily, 2021)
Have you listened to yourself recently?
Keywords: dept.hhs

The Complicated Process of Rejecting Heteronormativity | Dame Magazine - Schriefer, Natalie (Dame Magazine, 2021)
For 25 years, I thought I was a great proponent of LGBTQ+ rights. I supported queer friends and acquaintances; I stayed up to date on terms and phrasing; I asked for gender pronouns; I went to Pride. So when I had my first same-sex crush, I thought my transition from ally to community member would
Keywords: dept.hhs

Building Power for Health: CARE’s Community Health Leaders Program - Santilli, Alycia; Morales, Sofia I.; Hodgson, Nora; Williams, Janice M.; Alvarez-Diaz, Isabel; Cole, Ayeisha; Abrams, Jasmine; Breny, Jean M.; O’Connor Duffany, Kathleen (Health Promotion Practice, 2026)
Individuals who face the daily impact of health inequities and their social drivers have knowledge and invaluable insights about solutions that are feasible at the local level. Community organizing is a dynamic and proven approach for building power among residents to identify community priorities, advocate for change, and co-create solutions to community issues, which has been applied to advance community priorities in the public health field. To build on evidence and further cultivate a pathway to strengthen community power and capacity within a public health framework, the Community Alliance for Research and Engagement (CARE), a health equity-focused partnership among Southern Connecticut State University, Yale School of Public Health, and the New Haven community, developed and implemented a new initiative, the Community Health Leaders (CHL) Program. The CHL program provides a model for community-centered leadership development as a strategy for advancing health equity. By equipping residents with the skills and support needed to advocate for change, CHL contributes to strengthening community power. Ultimately, continued investment in programs like CHL has the potential to create responsive public health programs and policies, reduce health inequities, and improve health outcomes. © 2026 Society for Public Health Education
Keywords: advocacy; community health; community organizing; dept.hhs; empowerment; health disparities; health equity; health promotion; lay leader advisors; social determinants of health; training

Introducing “Preservice Pipeline”—Why This Column, Why Now - Knipe, Bob (Journal of Physical Education, Recreation and Dance, 2026)
Future professionals learn to lead through a variety of professional opportunities, and it is time that JOPERD provides a forum dedicated to their development and an opportunity for them to lead as authors and coauthors. This article describes the new Preservice Pipeline column and how to submit articles. © 2026 SHAPE America.
Keywords: dept.hms

Utilizing the program impact pathways framework for improving COVID-19 vaccine confidence and uptake: demonstrations of multi-sector collaboration from two geographies in Connecticut - Beaulieu, A.; LaMonaca, Katherine; Higginbottom, Jackson; Foster, Jaime; Macklin, Bernard; Muhammad, Tila; Schwartz, Elizabeth; Comerford, Beth; Santilli, Alycia; Duffany, Kathleen; Pérez‐Escamilla, Rafael (Vaccine, 2025)
Keywords: 2019-20 coronavirus outbreak; Biology; Coronavirus disease 2019 (COVID-19); Infectious disease (medical specialty); Medicine; Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2); Virology; dept.hhs

The Business Case for Breastfeeding: Identifying Which Barriers and Facilitators Employers Prioritize When Supporting Breastfeeding Employees in the Workplace - Frieson, Tomeka; Muhammad, Tila; Belyea, Monica; Cole, Ayeisha; Ray, Natasha; Duffany, Kathleen (Journal of Human Lactation, 2026)
Keywords: Breast feeding; Breastfeeding; Phone; Private sector; Public health; Space (punctuation); breastfeeding; breastfeeding barriers; breastfeeding benefits; breastfeeding experience; breastfeeding knowledge; breastfeeding promotion; breastfeeding support; dept.hhs; maternal health; public health; qualitative methods; social support

Komi Can't Communicate: Making Friends and Not Scaring People - Oda, Tomohito; Schriefer, Natalie (2026)
Learn to make friends and stop scaring people away with this clever book inspired by the hit manga Komi Can’t Communicate.Do you find it hard to sp...

Empowering the self: Flow state in The Legend of Zelda: Breath of the Wild and Tears of the Kingdom - Schriefer, Natalie (Journal of Gaming & Virtual Worlds, 2026)
Keywords: Creativity; Flow (mathematics); Identification (biology); Legend; State (computer science); Tears; dept.hhs

Listening to Community to Improve Breastfeeding Friendliness: Findings From a Community Readiness Assessment on Breastfeeding - Frieson, Tomeka; Masterson, Amelia; Tran, Victoria; Douglass, Frankie; Duffany, Kathleen (Health Promotion Practice, 2025)
Breastfeeding is a key nutritional behavior for infants during their first years of life. While prenatal breastfeeding intentions do not differ significantly between non-Hispanic Black and White mothers, the ability to meet those intentions decreases over time, and to a greater extent among Black mothers. This is partially due to environments inadequately supportive of individuals' breastfeeding needs (i.e., not breastfeeding-friendly). The Community Readiness Assessment is a powerful tool to assess a community's readiness to take action on pressing health issues. While it is frequently used to understand readiness to prevent negative health outcomes, this study explores how it can be used to understand readiness to promote breastfeeding friendliness and subsequently identify appropriate intervention strategies. Between November 2020 and June 2021, we conducted interviews with 23 key respondents in New Haven, Connecticut, representing five community sectors. Respondents scored five dimensions of readiness on a 9-point scale (1 = no awareness, 9 = community ownership). The overall community readiness score was 4.2, denoting the "preplanning" stage of readiness. The highest-scoring readiness dimension was "community knowledge about the issue" (mean score: 4.5), and the lowest-scoring dimension was "resources related to the issue" (mean score: 3.3). Small business owners reported the highest readiness score by sector (mean score: 5.0), while large employers reported the lowest (mean score: 3.1). Scores stratified by both sector and dimension revealed specific areas within the community where readiness-level-appropriate interventions could be implemented. This study highlights the benefit of assessing community readiness prior to intervention to identify tailored, equitable, and effective intervention strategies.
Keywords: Active listening; Breast feeding; Breastfeeding; Breastfeeding promotion; Community Readiness Assessment; Community health; Intervention (counseling); Psychological intervention; Scale (ratio); breastfeeding; breastfeeding-friendly; community; community assessment; community readiness; dept.hhs; public health practice

Flash Fiction: How to Build a Pyramid Fire in the Rain by Natalie Schriefer - Schriefer, Natalie (JMWW, 2021)
Do not walk away from this burgeoning hope of heat and dryness.
Keywords: dept.hhs

Dear Mx. Ortiz – Compressed - Schriefer, Natalie (2021)
Keywords: dept.hhs

The First Step - Schriefer, Natalie (2023)
From a snowbank I watched the squirrel run.
Keywords: dept.hhs

Catch the Moon - Smith, Ed Diane (Independently published, 2020)
Grey Sparrow Press, in this landmark book, cherishes the voices of national writing treasures published over ten years; Robert Bly, Robert Wexelblatt, Michael C. Keith, Jules Nyquist, Khem Aryal, Marie Sheppard Williams [posthumously,] Doug Holder, Momila Joshi, William Woolfitt, Thomas R. Smith, M.J. Iuppa, LB Chhetri, John Roche, and Bhisma Upreti to name a few. Grey Sparrow Press was formed as a non-profit 501[c]3 on May 11, 2009.
Keywords: dept.hhs

Career trajectories of women faculty who became academic administrators - Vancour, Michele L. (Advancing Women in Leadership Journal, 2023)
Women faculty often view academic leadership as incompatible with their work-life balance, detracting from research and teaching commitments, resulting in a loss of autonomy and an abandonment of discipline, promoting change in their relationships with colleagues, and placing an increased emphasis on budgeting, regulations and compliance (DeZure et al., 2014). Many researchers suggest that institutional culture works against leadership development for faculty, making the transition from faculty to administrator unlikely (Barden & Curry, 2013). It is increasingly important to identify the key factors that make the difference for women faculty to assume these roles. As such, in this study qualitative methods were employed to examine the experiences and career trajectories of 16 academic women who held tenured, fully promoted faculty positions prior to becoming administrators. The researcher found evidence to support future recruitment and retention in higher education leadership.
0 citations (Crossref) [2023-10-31]
Keywords: dept.hhs; peer-reviewed

Cold Reality: Revisions of War in John Knowles’ “Phineas” and A Separate Peace – Irish Journal of American Studies - Schriefer, Natalie (Irish Journal of American Studies, 2022)
Keywords: dept.hhs; peer-reviewed; ⛔ No DOI found

Breastfeeding Best Practices in Higher Education - Vancour, Michele L.; Griswold, Michele K. (Hale Publishing, 2014)
Keywords: Breastfeeding promotion; College environment; United States; dept.hhs; faculty_collection

Recognizing Mistreatment in Older Adults - Vandeweerd, C.; Firpo, Adolfo; Fulmer, Terry; Paveza, Gregory; Bolton, Marguarette (Handbook of Geriatric Assessment, 2006)
Keywords: Care; Diagnosis; Diseases; Handbooks; manuals; etc; Handbooks; manuals; etc; Older people; Older people; Psychological testing; United States; dept.hhs; faculty_collection

The implementation of a nutrition intervention in food pantries: the spirit of SWAP - Morales, Sofia I.; Vicente, Genesis; LaMonaca, Katherine; Rios, Jasmine; Cunningham, Shayna D.; Higginbottom, Jackson; Mathios, Erin; Werlin, Steve; Cramer, James; Santilli, Alycia; O’Connor Duffany, Kathleen (Health Promotion Practice, 2023)
Background. Food insecurity, affecting approximately 10% of the U.S. population, with up to 40% or higher in some communities, is associated with higher rates of chronic conditions and inversely associated with diet quality. Nutrition interventions implemented at food pantries are an effective strategy to increase healthy food choices and improve health outcomes for people experiencing food and nutrition insecurity. Supporting Wellness at Pantries (SWAP), a stoplight nutrition ranking system, can facilitate healthy food procurement and distribution at pantries. Purpose. Guided by the RE-AIM Framework, this study assesses the implementation and outcomes of SWAP as nutritional guidance and institutional policy intervention, to increase procurement and distribution of healthy foods in pantries. Method. Mixed-methods evaluation included observations, process forms, and in-depth interviews. Food inventory assessments were conducted at baseline and 2-year follow-up. Results. Two large pantries in New Haven, Connecticut, collectively reaching more than 12,200 individuals yearly, implemented SWAP in 2019. Implementation was consistent prepandemic at both pantries. Due to COVID-mandated distribution changes, pantries adapted SWAP implementation during the pandemic while still maintaining the ?spirit of SWAP.? One pantry increased the percentage of Green foods offered. Challenges to healthy food distribution are considered. Discussion. This study has implications for policy, systems, and environmental changes. It shows the potential for SWAP adoption at pantries, which can serve as a guide for continued healthy food procurement and advocacy. Maintaining the ?spirit of SWAP? shows promising results for food pantries looking to implement nutrition interventions when standard practice may not be possible.
0 citations (Crossref) [2023-10-31]
Keywords: dept.hhs; peer-reviewed

Coalition Building and Food Insecurity: How an Equity and Justice Framework Guided a Viable Food Assistance Network - Santilli, A.; Lin-Schweitzer, A.; Morales, S.I.; Werlin, S.; Hart, K.; Cramer, J.; Martinez, J.A.; O’Connor Duffany, K. (International Journal of Environmental Research and Public Health, 2022)
Food insecurity is widespread in the United States. The COVID-19 pandemic intensified the need for food assistance and created opportunities for collaboration among historically-siloed organizations. Research has demonstrated the importance of coalition building and community organizing in Policy, Systems, and Environmental (PSE) change and its potential to address equitable access to food, ultimately improving population health outcomes. In New Haven, community partners formed a coalition to address systems-level issues in the local food assistance system through the Greater New Haven Coordinated Food Assistance Network (CFAN). Organizing the development of CFAN within the framework of Collaborating for Equity and Justice (CEJ) reveals a new way of collaborating with communities for social change with an explicit focus on equity and justice. A document review exploring the initiation and growth of the network found that 165 individuals, representing 63 organizations, participated in CFAN since its inception and collaborated on 50 actions that promote food access and overall health. Eighty-one percent of these actions advanced equitable resource distribution across the food system, with forty-five percent focused on coordinating food programs to meet the needs of underserved communities. With the goal of improving access to food while addressing overall equity within the system, the authors describe CFAN as a potential community organizing model in food assistance systems. © 2022 by the authors.
3 citations (Crossref) [2023-10-31]
Keywords: chronic disease prevention; coalition building; dept.hhs; environment change; food insecurity; peer-reviewed; policy; systems

Core node location problem: Heuristic solvability via tabu search - Skorin-Kapov, J.; Skorin-Kapov, D.; Podnar, H. (International Journal of Operations and Quantitative Management, 2012)
We consider combinatorial problems arising in the design of Metro Core optical networks, dealing with the placement of specially equipped nodes capable of efficiently re-distributing the traffic. Two optimality criteria are considered: minimization of the maximal distance between two adjacent nodes, and minimization of the maximal path length. The paths are selected subject to the Quality of Service constraint implemented as the maximal hop length, and subject to survivability implemented as the request for having two edge disjoint paths. Integer programming formulations and a heuristic strategy based on tabu search are presented and solved either optimally using CPLEX 11.0 optimizer, or sub-optimally using a heuristic approach.
Keywords: Integer programming formulations; Meta-heuristic approach; Optical networks; Tabu search; dept.csc; ⛔ No DOI found

Physical mistreatment in persons with Alzheimer's disease - Vandeweerd, C.; Paveza, G.J.; Walsh, M.; Corvin, J. (Journal of Aging Research, 2013)
Physical mistreatment has been estimated to affect 2 million older persons each year and dramatically affects health outcomes. While researchers have attempted to examine risk factors for specific forms of abuse, many have been able to focus on only victim or perpetrator characteristics, or a limited number of psychosocial variables at any one time. Additionally, data on risk factors for subgroups such as persons with Alzheimer's disease who may have heightened and/or unique risk profiles has also been limited. This paper examines risk for physical violence in caregiver/patient dyads who participated in the Aggression and Violence in Community-Based Alzheimer's Families Grant. Data were collected via in-person interview and mailed survey and included demographics as well as measures of violence, physical and emotional health, and health behaviors. Logistic regression analysis indicated that caregivers providing care to elders with high levels of functional impairment or dementia symptoms, or who had alcohol problems, were more likely to use violence as a conflict resolution strategy, as were caregivers who were providing care to elders who used violence against them. By contrast, caregivers with high self-esteem were less likely to use violence as a conflict resolution strategy. Significant interaction effects were also noted. © 2013 Carla VandeWeerd et al.
34 citations (Crossref) [2023-10-31]
Keywords: African American; Alzheimer disease; Caucasian; Conflict Tactic Scale; Hispanic; adult; aged; alcoholism; article; caregiver; caregiver burden; conflict management; dementia; demography; depression; dept.hhs; emotion; female; functional disease; health behavior; human; interview; logistic regression analysis; major clinical study; male; mini mental state examination; named inventories; questionnaires and rating scales; patient abuse; physical capacity; priority journal; religion; risk factor; secondary analysis; self esteem; self report; social status; violence

The effects of sprint training and the Nordic hamstring exercise on eccentric hamstring strength and sprint performance in adolescent athletes. - Freeman, Brock W; Young, Warren B; Talpey, Scott W; Smyth, Andrew M; Pane, Calvin L; Carlon, Todd A (Journal of Sports Medicine and Physical Fitness, 2019)
BACKGROUND: Hamstring strain injuries (HSI) are among the most common injuries in field-based team sports with a high-speed running component. The implementation of the Nordic hamstring exercise (NHE) is a well-documented method of improving eccentric hamstring strength to mitigate the risk of HSI occurrence. Sprint training is specific to the injury mechanism and is thought to activate the hamstrings through maximal eccentric contractions. The purpose of this study was to compare the effects of sprint training and the NHE on eccentric hamstring strength and sprint performance., METHODS: Twenty-eight participants (mean+/-SD age=16.21+/-1.34 years; height=1.75m+/-0.10m; body mass=68.5kg+/-12.1kg) completed an eccentric hamstring strength assessment and 40m sprint to assess acceleration and maximum speed. Participants were randomly allocated to either a NHE training or sprint training group. Two sessions per week for four-weeks of training was performed with baseline testing procedures repeated in the week following the intervention. Perceptions of soreness were recorded following the warm-up in each training session., RESULTS: Both the NHE (effect size=0.39, P<0.05) and sprint training (effect size=0.29, P<0.05) groups displayed significant gains in eccentric hamstring strength. The NHE group reported trivial improvements in sprint performance, whilst the sprint training group experienced a moderate improvement, specifically in maximum speed (ES=0.83 Moderate). Sprint training also produced greater perceptions of soreness than the NHE following a four-week training intervention, specifically before the start of the last session (P<0.05)., CONCLUSIONS: These findings indicate that sprint training had a beneficial effect for both eccentric hamstring strength and sprint performance, whilst also producing greater soreness than the NHE following the final training session. It was concluded that a four-week block of maximum speed training may have both an injury prevention and performance enhancement benefit.
36 citations (Crossref) [2023-10-31] Place: Italy Freeman, Brock W. School of Health Sciences and Psychology, Faculty of Health, Federation University Australia, Ballarat, Australia - brockw.freeman@gmail.com. Young, Warren B. School of Health Sciences and Psychology, Faculty of Health, Federation University Australia, Ballarat, Australia. Talpey, Scott W. School of Health Sciences and Psychology, Faculty of Health, Federation University Australia, Ballarat, Australia. Talpey, Scott W. School of Health and Human Services, Southern Connecticut State University, New Haven, CT, USA. Smyth, Andrew M. School of Health Sciences and Psychology, Faculty of Health, Federation University Australia, Ballarat, Australia. Pane, Calvin L. Maribyrnong Sports Academy, Melbourne, Australia. Carlon, Todd A. Maribyrnong Sports Academy, Melbourne, Australia.
Keywords: *Hamstring Muscles/ph [Physiology]; *Muscle Strength/ph [Physiology]; *Running/ph [Physiology]; Adolescent; Athletic performance; Exercise; Exercise Test; Exercise Test/mt [Methods]; Exercise/ph [Physiology]; Female; Hamstring Muscles; Hamstring muscles; Humans; Male; Muscle Strength; Resistance training; Risk Factors; Running; Soft Tissue Injuries; Soft Tissue Injuries/et [Etiology]; Soft Tissue Injuries/pc [Prevention & Control]; Sports medicine; acceleration; accident prevention; adolescent; article; athlete; athletic performance; clinical article; controlled study; dept.hhs; eccentric muscle contraction; effect size; exercise; exercise test; female; hamstring muscle; human; male; muscle strength; peer-reviewed; perception; physiology; procedures; randomized controlled trial; resistance training; risk factor; running; soft tissue injury; sports medicine; warm up

Elder self-neglect and abuse and mortality risk in a community-dwelling population - Dong, XinQi; Simon, Melissa; de Leon, Carlos Mendes; Fulmer, Terry; Beck, Todd; Hebert, Liesi; Dyer, Carmel; Paveza, Gregory; Evans, Denis (JAMA-Journal of the American Medical Association, 2009)
Context Both elder self-neglect and abuse have become increasingly prominent public health issues. The association of either elder self-neglect or abuse with mortality remains unclear. Objective To examine the relationship of elder self-neglect or abuse reported to social services agencies with all-cause mortality among a community-dwelling elderly population. Design, Setting, and Participants Prospective, population-based cohort study (conducted from 1993 to 2005) of residents living in a geographically defined community of 3 adjacent neighborhoods in Chicago, Illinois, who were participating in the Chicago Health and Aging Project (CHAP; a longitudinal, population-based, epidemiological study of residents aged ¿= 65 years). A subset of these participants had suspected elder self-neglect or abuse reported to social services agencies. Main Outcome Measures Mortality ascertained during follow-up and by use of the National Death Index. Cox proportional hazard models were used to assess independent associations of self-neglect or elder abuse reporting with the risk of all-cause mortality using time-varying covariate analyses. Results Of 9318 CHAP participants, 1544 participants were reported for elder self-neglect and 113 participants were reported for elder abuse from 1993 to 2005. All CHAP participants were followed up for a median of 6.9 years (interquartile range, 7.4 years), during which 4306 deaths occurred. In multivariable analyses, reported elder self-neglect was associated with a significantly increased risk of 1-year mortality (hazard ratio [HR], 5.82; 95% confidence interval [CI], 5.20-6.51). Mortality risk was lower but still elevated after 1 year ( HR, 1.88; 95% CI, 1.67-2.14). Reported elder abuse also was associated with significantly increased risk of overall mortality (HR, 1.39; 95% CI, 1.07-1.84). Confirmed elder self-neglect or abuse also was associated with mortality. Increased mortality risks associated with either elder self-neglect or abuse were not restricted to those with the lowest levels of cognitive or physical function. Conclusion Both elder self-neglect and abuse reported to social services agencies were associated with increased risk of mortality. JAMA. 2009; 302(5):517-526 www.jama.com
290 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/064-145-016-708-660 tex.eissn: [object Object] tex.unique-id: [object Object]
Keywords: Activities of Daily Living; Aged; Aged; 80 and over; Cause of Death; Chicago; Cognition; Elder Abuse; Female; Humans; Male; Mandatory Reporting; Parkinson disease; Proportional Hazards Models; Prospective Studies; Risk; United States; Urban Population; abuse; aged; aging; article; cardiovascular disease; cause of death; cognition; cohort analysis; crime; daily life activity; demography; dept.hhs; diabetes mellitus; educational status; ethnic and racial groups; female; follow up; hazard ratio; hip fracture; human; hypertension; informed consent; longitudinal study; major clinical study; male; mandatory reporting; mortality; neoplasm; outcome assessment; physical activity; population based case control study; priority journal; proportional hazards model; prospective study; public health; research subject; risk; self neglect; social work; socioeconomics; statistics; stroke; urban population

Elder self-neglect: A discussion of a social typology - Paveza, Gregory; Weerd, Carla Vande; Laumann, Edward (Journal of the American Geriatrics Society, 2008)
This article presents a theoretical framework for the study of social and behavioral factors associated with elder self-neglect. The model presented reflects the authors' beliefs that a risk-vulnerability model offers a useful framework from which to study all forms of elder mistreatment, as well as elder self-neglect. This model has particular utility, because it can begin to define the elements of risk and vulnerability that may be addressed using preventative measures as opposed to solely addressing intervention, which is often the case when addressing elder mistreatment and self-neglect. The authors then address a method for using the Consortium for Research in Elder Self-neglect of Texas data as currently constructed and adding to that database to effectively study risks and vulnerabilities in the elder self-neglect population. These additional data would greatly expand the scope of the study. The discussant adds his perspective to the ideas proposed by the authors.
21 citations (Crossref) [2023-10-31] tex.unique-id: ISI:000261064700007
Keywords: Aged; Alzheimer disease; Elder Abuse; Elderly; Geriatric Assessment; Humans; Risk Adjustment; Self-neglect; Social Behavior; Social networks; caregiver burden; cognitive defect; conceptual framework; conference paper; daily life activity; data base; depression; dept.hhs; family violence; functional disease; gerontological research; home environment; human; mental disease; peer-reviewed; preventive health service; self neglect; social aspect; social psychology; social support; substance abuse

Do adult medicaid enrollees prefer going to their primary care provider's clinic rather than emergency department (ED) for low acuity conditions? - Capp, Roberta; Camp-Binford, Meredith; Sobolewski, Sarah; Bulmer, Sandra; Kelley, Lauren (Medical Care, 2015)
Background: The rates of annual visits for adult Medicaid enrollees to the emergency department (ED) are increasing. Many programs throughout the country are focused on engaging patients in the use of their primary care providers (PCP) rather than the ED for low acuity conditions. It is unclear, however, the proportion of patients who are willing to use primary care services rather than the ED if they are given the choice. Methods: Cross-sectional study of adult Medicaid enrollees (18 y and older) presenting to a large, urban, academic ED from June to August 2012 with a low acuity condition was performed. We excluded patients who did not have a PCP or active Medicaid insurance. Our primary goal was to determine the proportion of patients who prefer to use the ED, rather than their PCP clinic, if an appointment was immediately available. Our second goal was to understand why patients would prefer ED over PCP care. Results: A total of 150 patients agreed to complete the survey, and 95 (63.3%) met our inclusion criteria. Forty-three patients (45.3%) stated preferring to use their PCPs rather than the ED if an appointment was available at that time. Thirteen (48.1%) cited that the ED had more technology or specialty care services available when compared with their PCP's clinic, 8 (15.4%) were in significant pain, and 6 (11.5%) felt the care they received in the ED was better than what they would receive in their PCP clinic. Conclusions: Our study shows that a little less than half of adult Medicaid enrollees presenting to the ED with low acuity conditions would have preferred to use their PCP rather than the ED, if an appointment had been immediately available.
11 citations (Crossref) [2023-10-31] tex.eissn: 1537-1948 tex.unique-id: ISI:000354726500010
Keywords: Academic Medical Centers; Adult; Article; Continental Population Groups; Cross-Sectional Studies; Emergency Service; Hospital; Female; Health Services Accessibility; Humans; Male; Medicaid; Middle Aged; Patient Preference; Patient Satisfaction; Primary Health Care; United States; Urban Population; adult; ancestry group; cross-sectional study; dept.hhs; emergency department; emergency health service; emergency ward; female; health care availability; health care delivery; health service; health survey; human; major clinical study; male; medicaid; middle aged; pain; patient preference; patient satisfaction; primary care clinic; primary health care; primary medical care; priority journal; statistics and numerical data; technology; university hospital; urban population

A research update on correlates of heavy episodic drinking among undergraduate college students. - Montauti, Sara; Bulmer, Sandra Minor (American Journal of Health Education, 2014)
Despite prevention efforts of colleges and universities across the nation, there have been no substantial decreases in heavy episodic drinking among undergraduates over the past 2 decades.This study provides an update on correlates of heavy episodic drinking for a recent cohort of undergraduate college students.A cross-sectional survey design was utilized. Participants were randomly selected undergraduate students from a public 4-year university located in the Northeast.Heavy episodic drinking was associated with male gender, white race, having a family history of drug or alcohol abuse, smoking cigarettes, and using marijuana. Age, athlete status, completion of an alcohol education program, condom use, depression, anxiety, and financial stress were not associated. After controlling for gender and race, marijuana use and smoking cigarettes were found to increase predictability of heavy episodic drinking.Rates of heavy episodic drinking remain high but correlates may be shifting for this cohort of college students. Opportunities to address heavy episodic drinking concurrently with cigarette smoking and marijuana use should be explored.Qualitative research methods are needed to gain insight into reasons for heavy episodic drinking; information that could inform the creation of more effective programming. © 2014 Copyright © SHAPE America.
12 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/027-307-320-726-457 tex.type: [object Object]
Keywords: dept.hhs

Women's perceived benefits of exercise during and after breast cancer treatment. - Bulmer, Sandra Minor; Howell, Jeremy; Ackerman, Louise; Fedric, Regan (Women & Health, 2012)
Empirical data support the benefits of physical activity for women who have been diagnosed with breast cancer. However, the experience of exercising during or after breast cancer treatment has not been fully documented. The purpose of the researchers in this study was to provide an in-depth description of women's experiences with exercising during or after their breast cancer treatments, specifically, their perceptions of the benefits they experienced as a result of participation in an individualized exercise program that included cardiovascular and resistance activities. Forty-five women who had been diagnosed with breast cancer within the previous two years were recruited from two oncology practices after electing to enroll in an exercise program. Data were collected between September 2006 and August 2007 through in-depth interviews at various stages in the exercise program and analyzed simultaneously using thematic analysis methods. Whether in treatment or post-treatment, women attributed psychological, physical, and social benefits to their participation in the exercise program. Participants credited the program with helping them to feel better, regain control over their bodies and their lives, manage their emotions, and prepare them to live healthfully going forward. These results provide insight into the specific ways women experience exercise during and after their breast cancer treatments.
24 citations (Crossref) [2023-10-31] Place: United States Bulmer, Sandra Minor. Department of Public Health, Southern Connecticut State University, New Haven, CT 06515, USA. bulmers1@southernct.edu
Keywords: *Adaptation; Psychological; *Breast Neoplasms/px [Psychology]; *Exercise Therapy/px [Psychology]; *Resistance Training; Adaptation; Psychological; Adult; Breast Neoplasms; Breast Neoplasms/di [Diagnosis]; Breast Neoplasms/rh [Rehabilitation]; Breast Neoplasms/th [Therapy]; Exercise Therapy; Female; Health Care Surveys; Health Services Accessibility; Humans; Interviews as Topic; Middle Aged; Perception; Physical Fitness; Qualitative Research; Questionnaires; Resistance Training; San Francisco; Social Support; Stress; Psychological; Stress; Psychological/px [Psychology]; Surveys and Questionnaires; United States; adaptive behavior; adult; article; breast cancer; breast tumor; dept.hhs; exercise; female; fitness; health care delivery; health care survey; human; interview; kinesiotherapy; mental stress; middle aged; perception; psychological aspect; psychosocial; qualitative research; questionnaire; resistance training; social support; women's health

Young women's experiences living with polycystic ovary syndrome - Weiss, Theresa R.; Bulmer, Sandra Minor (JOGNN - Journal of Obstetric, Gynecologic, and Neonatal Nursing, 2011)
Objective: To explore the psychosocial effects of living with polycystic ovary syndrome (PCOS) through the experiences of young women diagnosed with this endocrine disorder. Design: A qualitative, phenomenological methodology was used. Data were obtained through personal, semistructured interviews. Setting: College campuses in New England. Participants: A purposive sample of 12 young women with PCOS age 18 to 23 years. Results: The following themes emerged from analysis of participants' responses: concerns for older self, feeling physically inferior, coping with symptoms, patient-provider relationship, seeking useable information and support, and coming to terms with a chronic condition. Conclusions: Participants in this study faced numerous physical, social, and emotional challenges on a daily basis. As these young women gathered information relevant to their needs, sought and received social support, and maintained their daily routines to improve their health and appearance, they came to terms with this chronic condition. Based on participants' relayed experiences, it became evident that a need exists for health care practitioners to include psychosocial support in a comprehensive holistic plan for the treatment of PCOS in adolescents and young women in their early twenties. JOGNN, 40, 709-718; 2011. DOI: 10.1111/j.1552-6909.2011.01299.x
35 citations (Crossref) [2023-10-31] tex.eissn: 1552-6909 tex.unique-id: ISI:000297575300007
Keywords: Adaptation; Physiological; Adaptation; Psychological; Adolescent; Adolescents; Age Factors; Attitude to Health; Cross-Sectional Studies; Female; Humans; Interpersonal Relations; Interviews as Topic; Lived experience; New England; PCOS; Polycystic Ovary Syndrome; Polycystic ovary syndrome; Psychosocial; Qualitative; Quality of Life; Quality of life; Risk Assessment; Self Concept; Severity of Illness Index; Social Support; United States; Urban Population; Young Adult; Young women; adaptation; adaptive behavior; adolescent; adult; age; article; attitude to health; comparative study; cross-sectional study; dept.hhs; female; hospitalization; human; human relation; interview; ovary polycystic disease; psychological aspect; quality of life; risk assessment; self concept; social support; urban population

The impact of caloric information on college student's fast food purchasing intentions - Zigmont, Victoria A; Bulmer, Sandra Minor (American journal of health education, 2015)
Background: Fast food establishments are available on many college campuses and, as a result, many students consume foods that are high in calories and contribute to unhealthy weight gain. Purpose: This study measured college students' knowledge of the calorie content for fast food items and whether the provision of calorie information for those foods influenced their future purchasing intentions. Method: Randomly selected undergraduate college students (N = 201) completed an online survey that measured baseline knowledge of calorie content for a fast food item and intention to purchase that item in the future. After provision of accurate calorie information, students were posttested for intention to purchase that item in the future. Results: The majority of students underestimated calorie content for fast food items. After receiving accurate calorie information, those who initially underestimated calorie content were significantly more likely to change their intention to purchase that food item in the future. Discussion: Many college students are interested in avoiding high-calorie fast food items but are uninformed about calorie content. Translation to Health Education Practice: Colleges should provide calorie information for fast food items at the point of purchase so that students can make informed decisions that will promote their health. © 2015, Copyright © SHAPE America.
3 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/080-184-250-213-713 tex.type: [object Object]
Keywords: dept.hhs; dept.pch

Using CBPR methods in college health research exploring excessive alcohol consumption - Bulmer, Sandra Minor; Barton, Barbara A; Liefeld, Julie; Montauti, Sara; Santos, Stephanie; Richard, Melissa; Hnath, Laura; Pelletier, Kara; Lalanne, Jude (Journal of Adolescent Research, 2016)
Community-based participatory research (CBPR) is a collaborative methodology that uniquely involves stakeholders in all stages of the research process. CBPR has been widely utilized in the field of public health, but not widely employed with college populations. This study utilized CBPR methods within a college community to gain insight into excessive alcohol consumption. Six student researchers planned and carried out a rigorous qualitative study at a public university in the Northeast region of the United States. A total of 48 undergraduate participants were recruited for focus groups that were facilitated by two student researchers, and transcribed and analyzed using thematic analysis methods. Students' reasons for drinking alcohol were focused within the themes of inclusion, habitual default, and the student development process. Social media, strict policy/enforcement, and student's desire to avoid responsibility led to increased risk and consequences related to drinking. Students recommended late night transportation and a Good Samaritan policy as strategies to improve student safety. This study led to student advocacy and policy change directed at improving student's health and safety and demonstrated that CBPR methods show promise for engaging students and producing meaningful data.
7 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/015-321-517-465-575 tex.type: [object Object]
Keywords: college issues; dept.hhs; dept.mft; emerging adulthood; health; qualitative methods; substance use

Correlates and Predictors of Depression and Anxiety Disorders in Graduate Students - Barton, Barbara A.; Bulmer, Sandra M. (Health Educator, 2017)
Depression and anxiety are increasingly prevalent on college campuses; however, few studies have explored these disorders among graduate students. Purpose of this study was to examine prevalence, correlates and predictors of depression and anxiety among graduate students. This cross-sectional study used secondary data (N=4477) collected as part of the Healthy Minds Study. The Patient Health Questionnaire (PHQ) was used as the screening instrument. Multiple logistic regression examined the effect of demographic and social variables on the outcome of screening positive. Results showed 14.0% screened positive for depression, 9.5% for anxiety, 19.1% for either, and 4.4% for both. Depression correlates included: race/ethnicity, nationality, living situation, relationship status and finances growing up. Anxiety correlates included: sex, nationality, sexual orientation, and current finances. Validated predictors for depression were relationship status and finances growing up. Validated predictor for anxiety was identifying as lesbian, gay, bisexual, transgender or queer (LGBTQ), while being male and international status were protective. These findings suggest depression and anxiety are as prevalent among graduates as undergraduates and provide insight into the social and demographic influences of screening positive. Health educators can use these findings to inform policy and programming for graduate students that will provide an appropriate combination of services.
Keywords: Anxiety Disorders; Case Studies; Correlation; Depression (Psychology); Ethnicity; Family Income; Foreign Students; Gender Differences; Graduate Students; Health Education; Health Services; Interpersonal Relationship; Minority Groups; Money Management; Place of Residence; Predictor Variables; Race; Sexual Identity; Sexual Orientation; dept.hhs; ⛔ No DOI found

Ten-year trends and differences in alcohol consumption among black and white female undergraduates - Barton, Barbara A; Bulmer, Sandra Minor; Mugno, Raymond; Misencik, Leann (Journal of Substance Use, 2019)
Background: Few studies have explored changing patterns of alcohol consumption among young females and differences based on race/ethnicity. Objective: This study examined differences in alcohol consumption between black and white undergraduate females and compared trends in three different measures of alcohol consumption over a 10-year period from 2004 to 2014. Methods: The CORE Alcohol and Drug Survey was used to collect data from female undergraduates attending a public university in the northeastern USA. Classes were randomly selected into the sample; class acceptance was 68% and student participation was 96%. The chi-square test examined differences between groups and the Cochrane Armitage Test for Trend assessed changes over time. Results: In 2014, for every measure of alcohol consumption examined, a significantly larger percentage of white females engaged in the behavior compared to black females. Trend analysis from 2004 to 2014 demonstrated a narrowing of this gap. Controlling for age, any alcohol use in past 30 days and binge drinking in the past 2 weeks increased significantly for black females 21 years or older. Any alcohol use in the past 30 days decreased significantly for white females under 21 years. Conclusion: These findings introduce many questions which should be explored through additional research.
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/102-626-859-619-803 tex.type: [object Object]
Keywords: Alcohol; Article; Black person; Caucasian; United States; adult; alcohol; alcohol consumption; binge drinking; college females; dept.hhs; dept.mat; dept.pch; drinking trends; female; human; major clinical study; peer-reviewed; priority journal; race difference; undergraduate student

The Power of Adapted Sports, Changing Attitudes in Higher Education: An Exploratory Study - Archambault, MaryJo; Searcy, Yan Dominic (Palaestra, 2018)
A wheelchair basketball showcase was hosted at a state university in New England. Student surveys revealed that the event had a positive effect on students’ views of both individuals with disabilities and adapted sports. Using Allport’s (1954) contact theory as a lens, the author demonstrates how the event met the four positive features that Allport believed should be present in order to reduce negative feelings toward another group: (a) equal status between the groups, (b) common goals, (c) intergroup cooperation and (d) the support of authorities. This exploratory study argues that adapted sports can be an effective method to positively impact stereotypical views of people with disabilities.Subscribe to PALAESTRA
Keywords: Adaptive sports; changing attitudes; contact theory; dept.hhs; dept.rec; higher education; peer-reviewed; ⛔ No DOI found

Substance use, anxiety, and depressive symptoms among college students - Walters, Kenneth S.; Bulmer, Sandra Minor; Troiano, Peter F.; Obiaka, Uzoma; Bonhomme, Rebecca (Journal of Child & Adolescent Substance Abuse, 2018)
Research on college substance use and mental illness is limited and inconsistent. Measures of substance use, and anxiety and depressive symptoms, were completed by 1,316 undergraduates within a major drug transportation corridor. Hierarchical linear regressions were used to test associations between anxious and depressive symptoms and substance use (i.e., alcohol, cannabis, tobacco, cocaine, other amphetamines, sedatives, hallucinogens, and designer drugs). Depressive symptoms were associated with use of cannabis, tobacco, amphetamines, cocaine, sedatives, and hallucinogens. Anxiety symptoms were unrelated to substance use. These findings support the need for education and prevention at universities, emphasizing tobacco, cannabis, and certain “harder” drugs.
58 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/158-625-507-666-259, pop00148 tex.type: [object Object]
Keywords: anxiety; college students; depression; dept.hhs; dept.psy; mental health; peer-reviewed; substance use

Right back like we left something: examining the commodification of Blackness in social services to address racial disparities - the case of Hartford - Searcy, Yan (Social Work in Public Health, 2018)
Market-based approaches to addressing racial disparities have essentially re-commodified Blackness. Utilizing Hartford, which contains the largest percentage of Blacks per capita in Connecticut, this article examines market-based approaches to address racial disparities while discussing Blackness as an enduring commodity that is tied to private sector profit. The study argues that market based approaches incentivize punitive approaches to social problems associated with Blackness. The study concludes by suggesting that addressing disparities utilizing markets requires reimagining policy incentives to focus on prevention and treatment of social problems associated with Blackness. Failure to reimagine policy incentives serves to commodify Blackness whereby industries benefit from the continuity of disparities rather than the elimination of disparities.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/037-350-903-962-757 tex.eissn: [object Object] tex.unique-id: [object Object]
Keywords: *African Americans; *Commodification; *Private Sector; *Social Justice; *Social Work/og [Organization & Administration]; African American; African Americans; Black person; Commodification; Connecticut; Culture; Humans; Private Sector; Public Policy; Racial disparities; Social Justice; Social Work; United States; article; blackness; commodification; cultural anthropology; dept.hhs; human; incentive; market; market conditions; organization and management; peer-reviewed; policy; private sector; privatization; profit; public policy; racial disparity; social justice; social policy; social problem; social services; social work

Historical persecution reaction complex: exploring a link between racial identity and poor leadership outcomes - Searcy, Yan Dominic; Hines, Resche D. (Journal of Black Studies, 2017)
This original study examines the reluctance of oppressed populations to publicly criticize the recognized performance shortcomings of leaders who are members of their identity group. Using critical race theory (CRT), this article utilizes three case examples of Black American leadership that present evidence of what the authors identify as Historical Persecution Reaction Complex (HPRC). HPRC describes four elemental arguments reflecting an oppressed identity group's attempt to protect itself from perceived further social marginalization, limit the exacerbation of oppression, and to preserve the identity group's leadership gains in the larger society by supporting leadership despite recognized shortcomings in the leadership. Although asserting HPRC operates as a functional reaction to oppression by serving both as an act of cohesion and resistance to oppressive structures, the authors suggest that HPRC is paradoxically detrimental to oppressed identity groups due to maintaining substandard leadership.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/062-966-244-733-329 tex.eissn: [object Object] tex.unique-id: [object Object]
Keywords: Black identity; antiracism; dept.hhs; leadership; oppression; racial identity